Habilidad lógica y mecanismos motivacionales en la evaluación de argumentos - Massolo, Alba (2024)
The main objective of this research is to analyze the myside bias in two argument evaluation tasks: one linked to the paradigm of formal reasoning and the other linked to the paradigm of informal reasoning. For this, we develop and apply a reasoning test that combines formal reasoning tasks with informal reasoning tasks. The test was administered virtually to a total of 138 participants. The results confirmed the two hypotheses of the study, namely, that motivational mechanisms prevail over logical ability in the tasks of evaluating arguments (both deductive and non-deductive) and that the myside bias is significantly accentuated in the task of informal reasoning.